2016
DOI: 10.1074/jbc.m115.675413
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomics Identified an NS5A Phosphorylation Site Involved in Hepatitis C Virus Replication

Abstract: The non-structural protein 5A (NS5A) is a hepatitis C virus (HCV) protein indispensable for the viral life cycle. Many prior papers have pinpointed several serine residues in the low complexity sequence I region of NS5A responsible for NS5A phosphorylation; however, the functions of specific phosphorylation sites remained obscure. Using phosphoproteomics, we identified three phosphorylation sites (serines 222, 235, and 238) in the NS5A low complexity sequence I region. Reporter virus and replicon assays using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
82
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(96 citation statements)
references
References 41 publications
13
82
1
Order By: Relevance
“…Aspartate mutations suggest that NS5A phosphorylation occurs in a sequential cascade where phosphorylation of one serine residue leads to phosphorylation of the other serine residues (12,21). In our previous proteomics study (22), we identified phosphorylation at S222, S235, and S238 with high confidence scores. Using genetic mutations, we found that alanine mutation at S235 blunted NS5A hyperphosphorylation and viral replication.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…Aspartate mutations suggest that NS5A phosphorylation occurs in a sequential cascade where phosphorylation of one serine residue leads to phosphorylation of the other serine residues (12,21). In our previous proteomics study (22), we identified phosphorylation at S222, S235, and S238 with high confidence scores. Using genetic mutations, we found that alanine mutation at S235 blunted NS5A hyperphosphorylation and viral replication.…”
mentioning
confidence: 86%
“…Using genetic mutations, we found that alanine mutation at S235 blunted NS5A hyperphosphorylation and viral replication. Single-alanine mutation at S222 or S238 did not have apparent effects; however, double mutations at S222 and S238 reduced NS5A hyperphosphorylation and viral replication (22), suggesting that phosphorylation events among these sites are interdependent. In the previous work, we generated an antibody specific to NS5A S235 phosphorylation and used it to show that S235 phosphorylation correlated with viral replication in time and intracellular locations (22).…”
mentioning
confidence: 89%
See 3 more Smart Citations